Installation of click-type functional groups enable the creation of an additive manufactured construct for the osteochondral interface. (1st January 2023) - Beeren, Ivo A O; Dijkstra, Pieter J; Lourenço, Ana Filipa H; Sinha, Ravi; Gomes, David B; Liu, Hong; Bouvy, Nicole; Baker, Matthew B; Camarero-Espinosa, Sandra; Moroni, Lorenzo
Abstract: Melt extrusion-based additive manufacturing (AM) is often used to fabricate scaffolds for osteochondral (OC) regeneration. However, there are two shortcomings associated with this scaffold manufacturing technique for engineering of tissue interfaces: (a) most polymers used in the processing are bioinert, and (b) AM scaffolds often contain discrete (material) gradients accompanied with mechanically weak interfaces. The inability to mimic the gradual transition from cartilage to bone in OC tissue leads to poor scaffold performance and even failure. We hypothesized that introducing peptide gradients on the surface could gradually guide human mesenchymal stromal cell (hMSC) differentiation, from a chondrogenic towards on osteogenic phenotype. To work towards this goal, we initially manufactured poly( ϵ -caprolactone)-azide (PCLA) and PCL-maleimide (PCLM) scaffolds. The surface exposed click-type functional groups, with a surface concentration in the 10 2 pmol cm −2 regime, were used to introduce bone morphogenic protein-2 or transforming growth factor-beta binding peptide sequences to drive hMSC differentiation towards osteogenic or chondrogenic phenotypes, respectively. After 3 weeks of culture in chondrogenic medium, we observed differentiation towards hypertrophic chondrogenic phenotypes with expression of characteristic markers such as collagen X. In osteogenic medium, we observed the upregulation of mineralization markers. In basic media, the chondro-peptide displayed a minor effect on chondrogenesis, whereas the osteo-peptide did not affect osteogenesis. In a subcutaneous rat model, we observed a minimal foreign body response to the constructs, indicating biocompatibility. As proof-of-concept, we finally used a novel AM technology to showcase its potential to create continuous polymer gradients (PCLA and PCLM) across scaffolds. These scaffolds did not display delamination and were mechanically stronger compared to discrete gradient scaffolds. Due to the versatility of the orthogonal chemistry applied, this approach provides a general strategy for the field; we could anchor other tissue specific cues on the clickable groups, making these gradient scaffolds interesting for multiple interfacial tissue applications.